La tentazione populista - Greblo, Edoardo (Scenari, 2021)
The concept of “populism” is elusive and controversial, and is commonly interpreted according to mutually exclusive perspectives. For some it opens up new possibilities for a bottom-up democracy capable of “returning the scepter to the prince”, that is to the people; for others it represents a threat to constituted representative democracies. The article suggests the idea that a possible way to escape the trap of opposing unilaterality is to offer a ““minimalist” definition, which applies to populism two of the eight conditions set by Robert Dahl to define “polyarchy”: “public contestation” and “inclusiveness”.